Capital imports composition, complementarities, and the skill premium in developing countries - Raveh, Ohad; Reshef, A. (Elsevier BV, 2016)
© 2015 Elsevier B.V.We study how the composition of capital imports affects relative demand for skill and the skill premium in a sample of developing economies. Capital imports per se do not affect the skill premium; in contrast, their composition does. While imports of R&D-intensive capital equipment raise the skill premium, imports of less innovative equipment lower it. We estimate that R&D-intensive capital is complementary to skilled workers, whereas less innovative capital equipment is complementary to unskilled labor-which explains the composition effect. This mechanism has substantial explanatory power. Variation in tariffs, freight costs and overall barriers to trade, over time and across types of capital, favors imports of skill-complementary capital over other types. We calculate that reductions in barriers to trade increase inequality substantially in developing countries through the composition channel.